Knowledge mapping of acupoint sensitization and acupoint specificity: a bibliometric analysis - Xuesong Wang; Xuxin Li; Yuanbo Gao; Di Wang; Di Wang; Jun Liu; Jun Liu; Xisheng Fan; Xisheng Fan; Hao Chen; Guang Zuo; Haiping Li; et al. (Frontiers in Neuroscience)
ObjectiveThe relationship between acupoint sensitization and acupoint specificity is a topic of significant interest in acupuncture research. Numerous clinical studies have demonstrated that needling pain sensitive acupoints yields superior therapeutic outcomes compared to traditional acupoints, particularly in the context of pain disorders. However, there is a lack of bibliometric analysis in acupuncture area. Therefore, the objective of this study is to offer a comprehensive overview of the knowledge structure and research hotspots pertaining to acupoint sensitization and acupoint specificity.MethodsThe search for publications pertaining to acupoint sensitization and acupoint specificity was conducted in the Web of Science Core Collection (WoSCC) database from its inception until August 11, 2023. Subsequently, bibliometric analyses were carried out using VOSviewer, CiteSpace, R software (Bibliometrix package), and GraphPad Prism software.ResultsThis study includes 4,940 articles from 72 countries, with China and the United States being the leading countries. The number of publications related to acupoint sensitization and specificity has been increasing annually. Major research institutions involved in this field include the Shanghai University of Traditional Chinese Medicine, Kyung Hee University, Beijing University of Chinese Medicine, Chinese Academy of Chinese Medical Sciences, and China Medical University, among others. “Evidence-based Complementary and Alternative Medicine” is the most popular journal in acupuncture field, and “PAIN” is the most co-cited journal. Publications are contributed by 20,325 authors from all over the world, with Wu Huangan, Fang Jianqiao, Lin Yi-Wen, Liu Huirong, and Chen Rixin having published the most articles. Han Ji-Sheng is the most cited author in this research area. The main directions include the study of temperature specificity of acupoints, the diagnosis of acupoint sensitization diseases, and the study of the mechanism of acupoint sensitization. The most listed keywords in recent years are “TRPV1,” “signaling pathway,” and “diagnosis.”ConclusionThis is the first bibliometric study to comprehensively summarize research trends and advances in acupoint sensitization and acupoint specificity, and the information highlights recent research preliminary and main directions that serve as a reference for acupoint sensitization and acupoint specificity research.